Poétiques mémorielles et imaginaire collectif : canne à sucre et émancipation en Caraïbe - Sandra Monet-Descombey Hernández (Caravelle)
By means of the recurring theme of sugar cane which appears in all contemporary literature from the Caribbean islands, this article will emphasise upon the emergence of a memorial poetics turned towards the past instead of looking forward towards the 21st century, as a way of recovering their identity through colonial history (slavery) and post-colonial one (independences, cultural and political revolutions) up to the present century. The sugar plantation (economy, society, identity) tends to disappear from current landscapes but still represents a symbol of historical resistance as well as the common expression of interregional Caribbean identity; besides, it remains a reconceptualized theme in the theoretical essays of many Caribbean authors from the beginning of the 21st century until today.